METHODOLOGICAL APPROACH TO THE ASSESSMENT OF SPATIAL AND TEMPORAL PARAMETERS OF AN UNMANNED AERIAL VEHICLE DURING FLIGHT TESTS - Zirka, Andrey; Zirka , Mariia; Kadet , Natalia (Science-based technologies, 2023)
During flight tests of unmanned aerial vehicles (UAVs), the assessment of individual parameters, such as: range and flight duration (spatial and temporal parameters) is associated with the involvement of a significant resource (time, space, material and technical, etc.), which often raises problematic questions regarding their implementation. At the same time, in most cases, the customer usually puts forward fundamental and clear requirements to ensure the required range and duration of the flight. These indicators generally characterize the capabilities of complexes to perform tasks as intended. However, during the conducted tests, for a number of complexes, they were not fully evaluated (confirmed), including due to unfavorable conditions for conducting tests, as well as the presence of space and time limitations, first of all, the imperfection of the existing testing facilities. Given the above, the article substantiates, builds and analyzes the practical implementation, based on the results of a flight experiment, of a methodological approach to the operational assessment of certain flight characteristics, primarily the range and duration of flight during UAV flight tests. At the same time, an increase in the reliability of the data obtained is achieved through the use of the proposed complex indicator and savings in material and time resources due to the optimization of the program of the relevant test flights. The previously proposed complex indicator - the coefficient of technical perfection of the UAV, which simultaneously takes into account the perfection of the design, aerodynamic layout and efficiency of the power plant, allows to verify the reliability of the values of the parameters of the maximum range and duration of the UAV flight obtained during flight tests The theoretical and practical calculation (during a flight experiment) of the coefficient of technical perfection of a UAV with an electric propulsion system based on the experimentally obtained characteristics of the maximum range and duration of flight is presented and compared.